Fear, Anxiety and the State of Terror - Aly, Anne; Green, L. (Routledge Taylor and Francis, 2010)
The 11 September 2001 terrorist attacks on the World Trade Center and the Pentagon marked the advent of an unprecedented preoccupation with terrorism. Although Australia's actual terrorist risk profile remains marginal in comparison with other mortality risks, in times of crisis, the reasoned negotiation of risk is marginalised. Drawing on the findings of qualitative research, this article offers an analysis of how Australians are responding to the threat of terrorism embodied in a developing discourse of the war on terror and how they construct their perceptions of terrorist risk. The findings implicate community fear as a factor that should be considered in the development of counter terrorism strategies that emphasize community engagement as a mechanism for challenging radicalisation in democratic states.